Reptile embryos are not capable of behavioral thermoregulation in the egg. Issue 1 (1st December 2017) - Cordero, Gerardo A.; Telemeco, Rory S.; Gangloff, Eric J.
Abstract : Reptile embryos have recently been observed moving within the egg in response to temperature, raising the exciting possibility that embryos might behaviorally thermoregulate analogous to adults. However, the conjecture that reptile embryos have ample opportunity and capacity to adaptively control their body temperature warrants further discussion. Using turtles as a model, we discuss the spatiotemporal constraints to movement in reptile embryos. We demonstrate that, as embryos grow, the internal egg space rapidly diminishes such that the temporal window for appreciable displacement is confined to stages that feature incomplete neuromuscular differentiation. During this time, muscles are insufficiently developed to actively and consistently control movement. These constraints are well illustrated by the Chinese softshelled turtle ( Pelodiscus sinensis ), the first reptile reported to behaviorally thermoregulate. Furthermore, sporadic embryo activity peaks after the temperature‐sensitive period in species with temperature‐dependent sex determination, thus nullifying the opportunity for embryos to exhibit control over this important phenotype. These embryonic constraints add to previously‐identified environmental constraints on behavioral thermoregulation by reptile embryos. We discuss alternative hypotheses to explain previously reported patterns of behavioral thermoregulation. Based on a holistic consideration of embryonic limitations, we conclude that reptile embryos are generally unable to adaptively behaviorally thermoregulate within the egg.